The Evaluation of Building’s Structural Reliability of Masjid Tuha Indrapuri, Aceh Besar - Riza Aulia Putra; Saiful Hadi (Elkawnie: Journal of Islamic Science and Technology, 2019)
Masjid Tuha Indrapuri is one the ancient mosques in Aceh located in the district of Aceh Besar. The precise location of the mosque is in Indrapuri, Aceh Besar. Masjid Tuha Indrapuri exists right in the complex of the former temple. This mosque was built on an area of 33,875 square meters using the wooden material. The construction is supported by 4 (four) main pillars (that in terms of Javanese architecture known as “Soko Guru”) with the shape of an octagonal cross section. Given the age of the mosque that is quite old, the structural reliability of the mosque structure has certainly been worn off, especially in the column and beam structure. The condition of several columns and beams is currently tilted. In this study, an assessment of the robustness of the buildings was performed using forensic engineering method. The purpose of this study is to evaluate the reliability of this old mosque so that the data related to every of its structural component can be obtained. Through this evaluation, it was expected that the strategy or treatment that needs to be planned to the building could be determined, therefore at the end, it can continuously stand as its ideal condition.